Evaluation of Turkish videos about breast self-examination on YouTube - Ulutaş, Mehmet Eşref; Balcı, Eray (The European Research Journal, 2024)
Objectives: Breast self-examination (BSE) is very important to early detect breast cancer in women in addition to imaging methods. The easiest way to access information concerning how to perform this examination is undoubtedly the internet, and the most popular platform is YouTube. However, the most important disadvantage of this massive platform is the risk of spreading false information since it cannot be audited. This study aimed to evaluate Turkish videos on BSE on YouTube in terms of quality and content. Methods: On January 17, 2022, a search was conducted on YouTube using the keyword “breast self-examination”, and the first 210 videos presented on the first five pages were obtained. After applying the study criteria, 156 were included in the sample and evaluated by two general surgeons in terms of educational value, content, and upload source. Results: Of the 156 videos, 23 were categorized as useful (14.7%) and 133 as misleading (85.3%). When examined according to the upload source group, universities/professional organizations/non-profit physicians/physicians had the highest rate of misleading videos (96.9%), while stand-alone health information websites had the highest rate of useful videos (24%). There was no significant difference between the upload sources in terms of video length, number of views, content score, or quality score. Conclusions: The number of useful Turkish videos on BSE is very low. Our results indicate the need for more educational and useful videos to be produced, especially by healthcare professionals who use the YouTube platform.